2017
DOI: 10.3892/mmr.2017.7080
|View full text |Cite
|
Sign up to set email alerts
|

Associations between mutations of the cell cycle checkpoint kinase 2 gene and gastric carcinogenesis

Abstract: Gastric cancer is the most common malignant tumor of the digestive system. The etiology of gastric cancer is complex, and susceptibility at the genetic level remains to be fully elucidated in genetic investigations. In the present study, mutations of the cell cycle checkpoint kinase 2 (CHEK2) gene and its association with gastric cancer were examined. Reverse transcription‑quantitative polymerase chain reaction technology was used to detect the expression of CHEK2 and it was found that the expression of CHEK2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…In this study, we also showed the clinical significance of two hub genes (CHEK2 and PLK1) in the cell cycle pathway and their correlations with FAM189B. Both of these two coexpressed genes of FAM189B have been well reported to play essential roles in the cell cycle regulation and development of GC [30][31][32][33][34]. Although there was only preliminary evidence of a correlation, this finding also suggests that FAM189B may affect the clinical progression of GC by disturbing the cell cycle of GC cells.…”
supporting
confidence: 55%
“…In this study, we also showed the clinical significance of two hub genes (CHEK2 and PLK1) in the cell cycle pathway and their correlations with FAM189B. Both of these two coexpressed genes of FAM189B have been well reported to play essential roles in the cell cycle regulation and development of GC [30][31][32][33][34]. Although there was only preliminary evidence of a correlation, this finding also suggests that FAM189B may affect the clinical progression of GC by disturbing the cell cycle of GC cells.…”
supporting
confidence: 55%
“…Though in PPGLs, the function of CHEK2 gene has not been well characterized; however, CHEK2 role in cell proliferation and tumor suppression has been confirmed by various reports. Hong et al established a CHEK2-1100delC mutant, which promoted the gastric cancer cell proliferation, migration, and invasion, with downregulation of E-cadherin and upregulated vimentin expression, suggesting its possible role in altered biological behavior as epithelial mesenchymal transition (EMT) [ 21 ]. Another study reported the novel recurrent CHEK2-Y390 C mutant associated with increased breast cancer risk in Chinese population.…”
Section: Discussionmentioning
confidence: 99%